Corporate social responsibility (CSR) of PR in Syrian ang Russian telecommunication companies in crisis. A comparative analytical study on communication activities of MTN and MTC companies - Muzykant, V.L.; Mfarrej, F. (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ Literaturovedenie, zhurnalistika, 2018)
The question of corporate social responsibility of public relations especially in crises continues to be timely, as highlighted by recent controversies on this topic. Coming to terms with cases such as these relies on the task of defining corporate social responsibility, and more broadly figuring out which aspects of the PR’s social responsibility can be feasibly regulated. This study aimed to identify the concept of corporate social responsibilityin crises for the public relations departments of MTN and MTS, and the activities and programs implemented by these two companies to reflect their concept of corporate social responsibility towards their publics and community.